2018
DOI: 10.1007/s00125-018-4606-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-insulin receptor antibodies as potential novel therapies for human insulin receptoropathy using cell culture models

Abstract: Aims/hypothesis Bi-allelic loss-of-function mutations in the INSR gene (encoding the insulin receptor [INSR]) commonly cause extreme insulin resistance and early mortality. Therapeutic options are limited, but anti-INSR antibodies have been shown to activate two mutant receptors, S323L and F382V. This study evaluates four well-characterised murine anti-INSR monoclonal antibodies recognising distinct epitopes (83-7, 83-14, 18-44, 18-146) as surrogate agonists for potential targeted treatment of severe insulin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Although rhIGF-1 has also occasionally been used in older patients with heterozygous INSR defects [63,65], the long-term risks and benefits of these agents are unclear, and they have no place in therapy outside clinical trials in this group. Reactivation of some mutant INSR using monoclonal antibodies has been tested in models [66,67], and has promise for the future, but remains experimental.…”
Section: Insulin Signalling Defectsmentioning
confidence: 99%
“…Although rhIGF-1 has also occasionally been used in older patients with heterozygous INSR defects [63,65], the long-term risks and benefits of these agents are unclear, and they have no place in therapy outside clinical trials in this group. Reactivation of some mutant INSR using monoclonal antibodies has been tested in models [66,67], and has promise for the future, but remains experimental.…”
Section: Insulin Signalling Defectsmentioning
confidence: 99%
“…Inhibitory INSR antibodies are now in phase 1 human trials ( 10 ), while stimulatory antibodies have been shown to ameliorate diabetes in rodents ( 11 13 ) and primates ( 14 ). Given the high clinical need in recessive insulin receptoropathy, we previously assessed the effect of monoclonal anti-INSR antibodies ( 15 19 ) on a series of disease-causing mutant INSRs in cell culture models, corroborating and extending prior findings by demonstrating an action of antibodies against a panel of mutant receptors ( 20 ).…”
Section: Introductionmentioning
confidence: 65%
“…We previously demonstrated the ability of bivalent, specific anti-INSR antibodies to act as surrogate ligands on a series of mutant INSR in cell culture models ( 20 ), and we now report their evaluation in vivo in a novel mouse model of human insulin receptoropathy. The humanized mouse model of insulin receptoropathy was generated by using sequential viral infection to knockout endogenous Insr and, then, to re-express human INSR .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations